Salmonella enterica mediated epigenetic promotion of fibrosis is a novel factor in benign prostatic hyperplasia - Cong Zhu; Lu-Yao Li; Ming-Hui Shi; Cheng Fang; Lu Yang; Ting Li; Fei Li; Shi-Song Yang; Tian-Kun Wang; Dao-Jing Ming; Tong Deng; Hao-Yue Sun; et al. (Military Medical Research)
Abstract Background Fibrosis constitutes a significant pathophysiological mechanism in the clinical progression of benign prostatic hyperplasia (BPH) and represents a contributing factor to the ineffectiveness of prevailing pharmacological treatments. Emerging evidence suggests a close association between microbial presence and the development of fibrosis. Nonetheless, the potential involvement of microbes within prostatic tissue in the pathogenesis of BPH and prostatic fibrosis, along with the underlying mechanisms, remains unexplored. Methods Utilizing immunohistochemistry and microbial sequencing, we analyzed the microbes of prostate tissues from BPH patients with different degrees of prostate fibrosis and found that Salmonella enterica (S. enterica) was enriched in the high degree of prostate fibrosis. We developed prostate cell and animal models infected with the lipopolysaccharide of S. enterica (S.e-LPS) to assess its impact on prostate fibrosis. To elucidate the underlying functional mechanisms, we employed molecular biology techniques, including RNA degradation assays, N6-methyladenosine (m6A) dot blotting, RNA immunoprecipitation, and m6A immunoprecipitation. Results Microbial diversity differed between low- and high-fibrosis groups, with S. enterica showing the highest mean abundance among the four species that differed significantly. S.e-LPS was detected in S. enterica-rich prostate tissue and was found to significantly promote cell proliferation, cell contractility, lipid peroxidation, and the induction of ferroptosis. Animal experiments demonstrated that S.e-LPS infection led to pronounced hyperplasia of the prostatic epithelium, with epithelial thickness increasing to 1.57 times that of the sham group, and collagen fibrosis increasing to 2.84 times that of the sham group, thereby exacerbating prostatic tissue fibrosis in rats. In vitro experiments further revealed that S.e-LPS promoted prostate cell fibrosis by inducing ferroptosis. Mechanistically, it was determined that S.e-LPS regulates ferroptosis via AlkB homolog 5 (ALKBH5)-mediated m6A modification, which affects the stability of glutathione peroxidase 4 (GPX4) mRNA, thereby affecting prostatic fibrosis. Conclusion The findings of this study suggest that S. enterica promotes prostatic fibrosis through ALKBH5-m6A-GPX4-mediated ferroptosis. This research offers novel insights for the development of new therapeutic targets and personalized strategies for the prevention and treatment of BPH from the perspectives of microbes and epigenetics.